The Integration of Character Education in Junior High School Mathematics Curriculum Based on the ATONG (Amati Tanya Olah Nalar dan Gagas) Approach (Journal of Primary Education, 2019)
The implementation of character education in Indonesia show that students have not received proper and maximum character education services because the unavailabilities of integrated character mapped in a tiered and focused manner. This research conducts the integration of character values into the curriculum that is stated in the mathematics syllabus and learning devices for Junior High School grade VII, VIII, and IX that is based on ATONG (Amati Tanya Olah Nalar dan Gagas) in a tiered and focused manner. This research aims to design syllabus and learning devices based on the ATONG approach that integrated character education; produce a valid syllabus and learning devices; and test the effectiveness of the coordinate system learning based on the ATONG approach with Eliciting Activities model that integrated hard work character. This research refers to the Borg & Gall model (2003) which is modified into 5 steps. The learning devices test was conducted in sampling method in grade VIII SMP Kartika XII. The result of expert validation shows that the syllabus and learning devices are valid with a score of 3.60 which is considered as very good; the learning devices test results in an effective learning. This research is success to map characters in a focused and tiered manner on innovative mathematics learning. The mapping of specific cognitive and psychomotor abilities is indispensable because the mapping in the syllabus is still general.